Inter-industry analysis in the Korean flow-of-funds accounts - Jiyoung Kim (Journal of Economic Structures, 2017)
This study mainly aims to provide an inter-industry analysis through the subdivision of various industries in flow-of-funds (FOF) accounts. Combined with the Financial Statement Analysis data from 2004 and 2005, the Korean FOF accounts are reconstructed to form 'from-whom-to-whom' basis FOF tables, which are composed of 115 institutional sectors and correspond to tables and techniques of input-output (I-O) analysis. First, power of dispersion indices are obtained by applying the I-O analysis method. Most service and IT industries, construction, and light industries in manufacturing are included in the first-quadrant group, whereas heavy and chemical industries are placed in the fourth quadrant since their power indices in the asset-oriented system are comparatively smaller than those of other institutional sectors. Second, investments and savings, which are induced by the central bank, are calculated for monetary policy evaluations. Industries are bifurcated into two groups to compare their features. The first group refers to industries whose power of dispersion in the asset-oriented system is greater than 1, mainly light industries, IT, and service. On the other hand, the second group indicates that their index is less than 1, mostly heavy and chemical industries. We found that the net induced investments (NII)-total liabilities ratios of the first group show levels half those of the second group since the former's induced savings are obviously greater than the latter.
Keywords: C67; E01; E58; G30; 330; Inter-industry analysis; Flow-of-funds; Monetary policy evaluation